2018
DOI: 10.1002/mbo3.738
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic characterization of Escherichia coli isolated from mollusks in Brazil and the United States

Abstract: The aim of this study was to determine the serogroups, antimicrobial resistance and genetic diversity of Escherichia coli isolates from samples of bivalve mollusks collected along Santa Catarina coast, Brazil, and from the Chesapeake Bay, Maryland, USA. One hundred forty‐one E. coli isolates were characterized for serogroups with 181 specific O antisera and antimicrobial susceptibility using the disk diffusion method. The genetic diversity was assessed using pulsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
1
5
1
Order By: Relevance
“…Oliveira ( 2016) isolated E. coli strains from mussels collected in Santos and found a similar percentage (20%) of resistance to norfloxacin. Miotto et al (2019) reported 96% of susceptibility to norfloxacin in bivalves cultivated in Santa Catarina, higher than in the present study where 75% of E. coli strains were susceptible to the antimicrobial.…”
Section: Table 1 Mean Bacteriological Count Values Of Musselscontrasting
confidence: 83%
See 1 more Smart Citation
“…Oliveira ( 2016) isolated E. coli strains from mussels collected in Santos and found a similar percentage (20%) of resistance to norfloxacin. Miotto et al (2019) reported 96% of susceptibility to norfloxacin in bivalves cultivated in Santa Catarina, higher than in the present study where 75% of E. coli strains were susceptible to the antimicrobial.…”
Section: Table 1 Mean Bacteriological Count Values Of Musselscontrasting
confidence: 83%
“…There was also resistance of 33.33% of the strains to nitrofurantoin, higher than that of Miotto et al (2019) who found 12% of resistant strains.…”
Section: Table 1 Mean Bacteriological Count Values Of Musselsmentioning
confidence: 59%
“…Indeed, E . coli isolates resistant to third/fourth/fifth generation cephalosporins were recovered from bivalves collected from the environment ( Al-Sarawi et al, 2018 ; Miotto et al, 2019 ; Divya et al, 2020 ; Jeong et al, 2021 ), moreover from bivalve molluscan shellfish purchased at the market ( Yu et al, 2020 ). In addition, ESBL producing E .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported different antibiotic resistance patterns in isolates of different bacterial species (pathogenic or non-pathogenic to humans, autochthonous/allochthonous of the marine environment) recovered from bivalves throughout the world ( Vignaroli et al, 2016 ; Grevskott et al, 2017 ; Mani et al, 2018 ; Lozano-Leon et al, 2019 ; Miotto et al, 2019 ; Parthasarathy et al, 2021 ). Nevertheless, a comprehensive systematic review on the status of AMR to the main antibiotic classes in bacterial isolates cultured from bivalves is not available.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of cefepime-resistant E. coli was 1% in Brazil (33). In the African regions, the prevalence of cefepime resistant E. coli was 8.3% in Ghana and 64.5% in Bamako (34).…”
Section: Discussionmentioning
confidence: 99%